2010
DOI: 10.1242/jeb.041129
|View full text |Cite
|
Sign up to set email alerts
|

Predicting bite force in mammals: two-dimensional versus three-dimensional lever models

Abstract: SUMMARYBite force is a measure of whole-organism performance that is often used to investigate the relationships between performance, morphology and fitness. When in vivo measurements of bite force are unavailable, researchers often turn to lever models to predict bite forces. This study demonstrates that bite force predictions based on two-dimensional (2-D) lever models can be improved by including three-dimensional (3-D) geometry and realistic physiological cross-sectional areas derived from dissections. Wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
123
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(126 citation statements)
references
References 59 publications
3
123
0
Order By: Relevance
“…These results support the long-held suspicion that Thomason's (1991) jaw musculature method greatly underestimates bite force (see Therrien, 2005a;Ellis et al, 2008;Davis et al, 2010). However, the congruence between empirically determined and hollow-model-derived bite force values expressed relative to P. leo suggests that the jaw musculature method might produce accurate bite force estimates for this felid (see Sakamoto et al, 2010).…”
Section: Accuracy Of Bite Force Estimates Derived From Mandibular Forsupporting
confidence: 66%
See 1 more Smart Citation
“…These results support the long-held suspicion that Thomason's (1991) jaw musculature method greatly underestimates bite force (see Therrien, 2005a;Ellis et al, 2008;Davis et al, 2010). However, the congruence between empirically determined and hollow-model-derived bite force values expressed relative to P. leo suggests that the jaw musculature method might produce accurate bite force estimates for this felid (see Sakamoto et al, 2010).…”
Section: Accuracy Of Bite Force Estimates Derived From Mandibular Forsupporting
confidence: 66%
“…However, the congruence between empirically determined and hollow-model-derived bite force values expressed relative to P. leo suggests that the jaw musculature method might produce accurate bite force estimates for this felid (see Sakamoto et al, 2010). The poorer performance of the jaw musculature method has been ascribed to a variety of issues, such as the fact that the method: (1) does not account for interspecific variation in jaw muscle pennation, (2) assumes that muscle cross-sectional area and lever arm length correlate directly with bite force, and (3) considers the mandible as a two-dimensional object only, which overestimates the crosssectional area of the masseter and pterygoid muscles and underestimates the cross-sectional area of the temporalis muscle in many carnivorans (Wroe et al, 2005;Ellis et al, 2008;Davis et al, 2010;Tseng and Binder, 2010). Thus mandibular force profiles, particularly the hollow mandible model, are a more accurate and far simpler method to estimate bite force than Thomason's (1991) jaw musculature method.…”
Section: Accuracy Of Bite Force Estimates Derived From Mandibular Formentioning
confidence: 99%
“…Most of these studies have clearly demonstrated the link between osteology, muscular activity and biting performance at the intraspecific as well as interspecific levels (e.g. Herrel et al, 1999;Aguirre et al, 2002;Davis et al, 2010;Santana et al, 2010). Morphology has also been shown to be a driver of performance and fitness via intra-sexual competition (Herrel et al, 2010;Lailvaux et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Separated by at least 55 Myr of evolution [41], the two piscivorous species in the dataset (Noctilio leporinus and Myotis vivesi) have converged in cranial morphologies characterized by a short, broad and tall or dorsally projected rostrum, and broad zygomatic arches. This morphology results in a shorter out lever that is suited for producing high bite forces at low gapes [71,72], and potentially confers more resistance during cyclical molar chewing [73]. Consistent with these specializations, piscivorous bats feed using narrow gapes and masticate their prey for a prolonged period of time [25]; fishes are laterally compressed and contain sharp bones that could be harmful if not chewed meticulously before swallowing.…”
Section: Discussionmentioning
confidence: 90%